Innovative Forms of Remote Service in Russian Banks: Mobile Banking - Bataev, Alexey V. (International Review of Management and Marketing, 2017)
The paper deals with development a new form of clients' remote banking - Mobile Banking. The main tendencies and perspectives of mobile banking development in Russia are studied. The main criteria by which mobile banking applications are programmed are reviewed. The analysis of used operating systems for mobile banking applications is carried out. The aspects related to security issues of mobile applications for banks are considered. The volume of stolen money from clients who use mobile banking is analyzed. Keywords: financial institutions, mobile banking applications, operating systems, security, JEL Classifications: G21, O31